Understanding the performance of irrigation systems around homes. Issue 4 (1st October 2016) - Maheshwari, Basant
Abstract: This study examines factors that affect the efficiency of outdoor home irrigation in the Sydney Metropolitan Area (SMA). The irrigation systems of 50 home sites were monitored, over a five-month period for flow rate, start time, duration and irrigation date. The monitoring was for quantification of the water use for lawn, garden and other garden areas, understanding of the issues and factors that affect the performance of irrigation. Results show that hand watering was the most common method, accounting for 35% of the areas irrigated by homeowners. Both portable sprinklers and microjets accounted for 20% and fixed sprinklers and drip irrigation accounting for 11% and 8% respectively. The study has implications for developing suitable urban water management strategies, and significant opportunities exist for water conservation through appropriately designed educational programs and the installation of improved irrigation systems, especially for the areas that are smaller or used for home gardens.